Protective effects of accompanying proteins on light- and water-mediated degradation of Curcumin - Mirzaee, Farideh; Ashrafi Kooshk, Mohammad Reza; Rezaei-Tavirani, Mostafa; Khodarahmi, Reza (Archives of Advances in Biosciences, 2013)
Curcumin is a natural polyphenolic compound with anti-cancer, anti-inflammatory, and anti-oxidation properties. Low water solubility and rapid hydrolytic degradation are two challenges limiting use of curcumin as therapeutic agent. In the current study, the role of the Bovine Serum Albumin (BSA), β-lactoglobulin and casein, as food-grade biopolymers and safe drug delivery systems, on the physical activity of curcumin were surveyed. It appears that BSA and casein as protein vehicles are useful tools to increase stability of curcumin, as a health promoting agent.